Euro corporate bonds risk factors - Carolina Castagnetti; Eduardo Rossi (Università degli Studi di Pavia, Dipartimento di Economia Politica e Metodi Quantitativi (EPMQ), 2006)
This paper investigates the determinants of credit spread changes on bonds denominated in euro. The analysis is carried out using a panel data on euro bonds. We try to asses the relative importance of market and idiosyncratic factors in explaining the movements in credit spread. Because credit spread changes can be easily viewed as an excess return of corporate bonds over treasury, we adopt a factor model framework. We consider different approaches to the estimation of common factors using a panel of monthly redemption yields on a set of corporate bonds for a time span of three years. Our results suggest that the euro corporate market is widely heterogeneous and illiquid. Neither the issue specific factors nor the aggregate common factors appear important in determining credit spread changes. However, an unobserved common factor, identified as a liquidity factor seems to drive a relevant component of the systematic changes in credit spreads.
Keywords: G10; C33; 330; Euro Corporate Bonds; Cross Section Dependence; Common Correlated Effects; Yield Curve; Unternehmensanleihe; Kreditrisiko; Kapitaleinkommen; Euromarkt; USA